Pengaruh Model Pembelajaran Problem Based Learning (PBL) Terhadap Hasil Belajar Siswa OTKP Pada Mata Pelajaran Kearsipan Di SMKS Karya Bunda Mandiri Medan T.A 2022/2023 - Alfi Nura; Dame Triulina Hutasoit (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2023)
The problem of this research is the low learning outcomes of the class. This research aims to determine how the learning model influences student learning outcomes at Karya Bunda Mandiri Vocational School in Medan with a population of class XII OTKP students and a sample of 30 students. The research method is quantitative, and this type of research is ex post facto research. In carrying out research, the techniques used to collect data or information are observation techniques in schools and classes, interviews with teachers and students, distributing questionnaires and documenting information. The validity of the questionnaire is calculated using product moment correlation and Cronbach alpha to test the reliability of the questionnaire. Data analysis in this study used normality, linearity, multicollinearity, multiple linear regression tests and hypothesis testing, namely the T, F, and R2 tests. The research results prove a positive and significant influence of the PBL model on student learning outcomes through the F test. The PBL model influences learning outcomes through an F-calculation of 10.876 with a significance of 0.000, which means it simultaneously has a positive and significant influence on learning outcomes (hypothesis accepted). Then, through a partial test (test-test) with a t-count of 2.163, a significance of 0.04, means that it partially has a positive and significant effect on learning outcomes (the hypothesis is accepted). The R2 test result has a value of 0.546, which means it has a 54.6% influence on the learning outcomes of the class studied.